HTML and CSS Web standards solutions : a Web standardistas' approach - Murphy, Christopher, 1943- (Friends of ED ; Distributed to the trade by Springer-Verlag, 2009)
In this book you will learn how to assemble XHTML markup, create hand-coded style sheets, use semantic markup to build web pages, establish your own web address and embrace the power of Web Standardistas' to create well-designed web pages.